Tissue Engineering in Plastic Surgery - What Has Been Done - Juliana Catarina Almeida Ribeiro (2020)
The field of tissue engineering applies principles of engineering and life sciences for the development of functional biologic substitutes. The increasing need of tissue for challenging reconstructive surgeries places plastic surgeons' involvement as vital in the research and development of engineered constructs and subsequent use. This narrative review aims to summarize tissue engineering principles, to update on its current uses and breakthroughs, to approach its current limitations and possible future directions for this exciting new medicine's area. A MEDLINE literature search was conducted in October 2019 with the terms "tissue engineering"[Title/Abstract] AND "plastic surgery"[Title/Abstract], and included studies' reference lists were scanned. The articles included were about tissue engineering and plastic surgery, and had clinical pertinence. The search was restricted for human studies, however animal studies considered pertinent for this review were also included. Language was restricted to English and Portuguese. This revision addressed tissue engineering's uses in skin lesions, craniocervical defects, musculoskeletal defects, peripheral nerves lesions, vascular tissue defects and adipose tissue uses. Research in tissue engineering is increasing exponentially, however, and although there are already several engineered constructs available, its widespread clinical application is still a hope. More long-term studies that answer outstanding issues are needed in order for that to become reality.